2016
DOI: 10.15405/epsbs.2016.07.02.26
|View full text |Cite
|
Sign up to set email alerts
|

Students’ Engagement in Risky Online Behaviour: The Comparison of Youth and Secondary Schools’

Abstract: Nowadays adolescents use the Internet very often in their daily life activities what, according to the researchers, causes their engagement in risky online behaviour. Youth school's students may be at greater risks online as they generally come from socially riskier or single-parent families. Thus, the purpose of this study is to find out if there are any differences between youth and secondary schools' students' engagement in risky online behaviours. Research method -cross-sectional survey with a questionnair… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 16 publications
1
2
0
1
Order By: Relevance
“…The contextual factors identified by the specialists of a CDCC confirm the findings of other studies that adolescents raised in families at social risk are more likely to have a higher probability of exposure to risk on OSN (Notten & Nikken, 2014;Paluckaitė & Žardeckaitė-Matulaitienė, 2016). The authors of earlier studies (Pociūtė & Krancaitė, 2012;Wolak et al, 2008;Noll et al, 2013) also emphasize that poor culture of relationship in girls' families, the lack of understanding and comfort, painful experiences and dissatisfaction with the quality of their lives are essential factors determining adolescents' careless involvement in OSN and leading to the cases of girls' victimization on OSN.…”
Section: The Research Findingssupporting
confidence: 83%
See 1 more Smart Citation
“…The contextual factors identified by the specialists of a CDCC confirm the findings of other studies that adolescents raised in families at social risk are more likely to have a higher probability of exposure to risk on OSN (Notten & Nikken, 2014;Paluckaitė & Žardeckaitė-Matulaitienė, 2016). The authors of earlier studies (Pociūtė & Krancaitė, 2012;Wolak et al, 2008;Noll et al, 2013) also emphasize that poor culture of relationship in girls' families, the lack of understanding and comfort, painful experiences and dissatisfaction with the quality of their lives are essential factors determining adolescents' careless involvement in OSN and leading to the cases of girls' victimization on OSN.…”
Section: The Research Findingssupporting
confidence: 83%
“…Scientific studies (Notten & Nikken, 2014;Paluckaitė & Žardeckaitė-Matulaitienė, 2016;Pociūtė & Krancaitė, 2012;Wolak et al, 2008;Noll et al, 2013;Rosen, 2007) have identified the significance of the social context for risky involvement of adolescents in OSN: adolescents who are growing in dysfunctional and/or single-parent families often lack social skills; therefore, their participation on OSN is prone to higher risk exposures. Socio-cultural, economic, and educational crisis prevails in social risk families, and child development disorders are determined both by the objective situation in the society and by the subjective experiences of family members and their attitude to the crisis situation (Kovachevikj et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Risk behaviour on the Internet also includes cyberbullying and real-life meetings with people met in the online environment (Guadix-Gámez, Borrajo a Almendros, 2016). Paluckaitė and Matulaitienė (2016) have divided risk behaviour on the Internet into five basic forms: risky sexual behaviour, communication with strangers, sharing personal information, cyberbullying, and access to age-inappropriate websites.…”
Section: Types Of Risk Behaviour On the Internetmentioning
confidence: 99%
“…Paauglių pažeidžiamumas interneto socialiniuose tinkluose neatsiejamas nuo socialinio konteksto. Nedarniose ar nepilnose šeimose augantys paaugliai dažnai stokoja socialinių įgūdžių, todėl jų raiškai virtualioje erdvėje būdinga didesnė rizika (Notten ir Nikken, 2014;Paluckaitė ir Žardeckaitė-Matulaitienė, 2016). Rizikos grupės paaugliai socialinius tinklus vertina kaip būdą užmegzti asmeninius ir intymius ryšius, tačiau neįžvelgia ten slypinčių pavojų (Livingstone ir Helsper, 2008).…”
unclassified